Speed performance of single phase induction motor using variable frequency IGBT and MOSFET inverter / Nur Sharifah Firzada Sukirman - Sukirman, Nur Sharifah Firzada (2011)
This paper presents speed performance of single phase induction motor using variable frequency IGBT and MOSFET inverter. The speed is varied from 35Hz to 65Hz by adjusting PWM inverter. The PWM inverter is controlled to produce a desired sinusoidal voltage at a particular frequency, which is filtered by a series inductance and a shunt capacitor. The simulation results are presented using Matlab/Simulink R2010a. The results show that the IGBT inverter is slightly difference compared to the MOSFET inverter in terms of the single phase induction motor rotor speed performance. The total harmonic distortion, THD spectrum for the input current of MOSFET is much better than the input current IGBT using different value of inductance and capacitor as the passive filter.